A nomogram predicting subclinical extension of cutaneous squamous cell carcinoma in Chinese individuals: A retrospective study. Issue 7 (19th February 2021) - Lin, Pingping; Zhu, Sainan; Zhang, Guohong; Huang, Yuanshen; Tu, Ping; Yang, Shuxia; Li, Hang
Abstract : Abstract: Cutaneous squamous cell carcinoma usually extends beyond the visible margin. Little is known about the predictors for cutaneous squamous cell carcinoma with subclinical extension in Chinese individuals. This study aimed to construct a nomogram for predicting the probability of subclinical extension of cutaneous squamous cell carcinoma in Chinese patients. A retrospective analysis was conducted using data from Mohs micrographic surgery-treated cutaneous squamous cell carcinoma patients at a single institution between December 1, 2009 and October 31, 2019. Subclinical extension was defined as a lesion requiring ≥ 2 Mohs stages or with final safe margins of ≥ 5 mm. A nomogram predicting the probability of subclinical extension was constructed using the predictors identified in multivariable analysis. Of 274 patients included, 119 (43.4%) had subclinical extension. In multivariable analysis, male sex (odds ratio [OR], 2.45; 95% confidence interval [CI], 1.40–4.29; P = .002), lesions on mucocutaneous areas (OR, 3.71; 95% CI, 1.34–10.32; P = .012) and extremities (OR, 2.40; 95% CI, 1.20–4.78; P = .013), maximum diameter of 10 to 19 mm (OR, 14.15; 95% CI, 4.24–47.28; P < .001), and 20 to 29 mm (OR, 9.21; 95% CI, 2.80–30.29; P < .001) were associated with subclinical extension. A nomogram incorporating these 3 variables demonstrated promising predictive ability (C statistics = 0.78; 95% CI, 0.67–0.89). The nomogram incorporating sex, tumor location, and maximum diameter can provide individualized prediction for subclinical extension in Chinese patients with cutaneous squamous cell carcinoma. This information may help surgeons determine appropriate margins at the first Mohs stage.